Genetic testing for forecasting and course of the chronic heart failure against the background arterial hypertension - A. L. Khokhlov; Yu. V. Rybachkova (Регуляторные исследования и экспертиза лекарственных средств, 2018)
Traced the impact of genetic testing on the course of chronic heart failure in patients with arterial hypertension. Evaluated the clinical significance of the frequency of gene polymorphisms in patients with the chronic heart failure, depending on the success of treatment. All patients were refined risk factors were performed general clinical methods, electrocardiography (ECG), ECG monitoring, echocardiography, pharmacogenetic testing, analysis of outpatient pharmacotherapy for 1 year and 5 years. The use of genetic testing to determine the course of chronic heart failure, its prognosis and timely in view of the personalized approach to carry out the correction of pharmacotherapy in accordance with existing clinical guidelines and standards.